Implementing the Cooperative Learning type Scramble Method to Enhance Arabic Sentence Writing Skills - Ardiansyah, Muhammad; Sholihah, Faizatun; Marlina, Leny (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
This study is a solution to the problem of low Arabic sentence writing skills in class V MI Hamzanwadi East Lombok. Among the factors causing this is the lack of writing practice, and teachers also often face obstacles in teaching writing Arabic sentences that are effective and interesting for students. The purpose of the study was to evaluate in detail the improvement and implementation of the scramble method in improving Arabic sentence writing skills of the material